PENGEMBANGAN BAHAN AJAR SMA BERBASIS AL QURUN TEACHING MODEL (ATM) PADA KONSEP MATERI LOGARITMA - Muhammad Kosim Ali; Laila Maharani; Rizki Wahyu Yunian Putra (Journal of Mathematics Education and Science, 2019)
In mathematics learning, there are a lot of complictaed problems such as students have difficulties in learning, students’ lack of interest, lack of practice and exercises, group and individual assigments that has not achieved the learning goal and lack of teaching material. Based on the students; score in daily test of SMA N 1 Bangun rejo, there are many students not qualified in achieveing minimum criteria competence (KKM) especially in logaritma. This reserach aims to invesitigate the worthiness of teaching materials based on ALQURAN teaching Model (ATM) on logaritma concept. It also aims to know the effectiveness of teaching and learning based on ALQURAN teaching Model (ATM). This research is classified as Research and Development (R&D) which implies ADDIE Model. There are five stages in developing namely 1). Analysis, 2). Design, 3). Development, 4). Implementation, 5). Evaluation. The instrument of this research was validation questionnaire which was given to material experts, media experts, and language expert. It aims to know and test the worthiness of the product. The instrument also was given to the students and teachers. It aims to know the interestingness of the product which has been developed.. Pretest and posttest were also given to them. Based on data analysis, especially from the experts, it can be said that the product is worthy to be used. The data from the students and teachers also imply that the product is worthy to be implemented and used. They said that it is very interesting. Based on the analysis about the effectiveness of the product, it can be said that class which was taught by implementing and using teaching material based ATM model on logarithm concept got Es = 0,30 in range 0,20 < Es ≤ 0,80. Dealing with the level of effectiveness, the sum of Es class which implied the product was classified as effective. Pembelajaran matematika yang terjadi saat ini belum maksimal dikarenakan peserta didik merasa sulit, tidak tertarik, kurangnya pemberian dan pengembangan latihan-latihan serta tugas secara individu maupun berkelompok yang dapat mengimplementasikan konsep dan materi serta kurangnya bahan ajar. Dari hasil data hasil ulangan harian peserta didik SMA N 1 Bangun Rejo banyak peserta didik yang tidak melampaui nilai KKM pada materi logaritma. Tujuan penelitian ini adalah untuk mengetahui kelayakan, kemenarikan bahan ajar berbasis ALQURUNTeaching Model(ATM) pada konsep Logaritma serta efektivitas pembelajaran yang diterapkan bahan ajar berbasis ALQURUNTeaching Model(ATM) pada konsep Logaritma. Metode dalam penelitian ini adalah penelitian dan pengembangan (R&D) dengan model pengembangan ADDIE. Ada 5 tahap dalam pengembangan ini yaitu 1) Analysis, 2) Design, 3) Development,4) Implementation, dan 5) Evaluation. Instrumen pengumpulan data yang digunakan adalah angket validasi yang diberikan kepada ahli materi, ahli media dan ahli bahasa untuk mengetahui kelayakan produk, dan diberikan kepada peserta didik dan pendidik, untuk mengetahui kemenarikan produk yang telah dikembangkan serta intrumen tes pretes dan posttes. Berdasarkan analisis data yang diperoleh dari ahli materi, ahli media dan ahli bahasa dinyatakan bahwa bahan ajar yang dikembangkan layak untuk digunakan, dan analisis data yang diperoleh dari peserta didik dan pendidik dinyatakan bahwa bahan ajar yang dikembangkan sangat menarik. Hasil analisis efektivitas data kelas yang diterapkan pembelajaran menggunakan bahan ajar berbasis ATM pada konsep materi logaritmadengan menghitung Effect Size diperoleh nilai dalam rentang, berdasarkan kategori yang ditentukan tingkat efektifitas besarnya kelas yang diterapkan pembelajaran yang diterapkandikategorikan cukup efektif dengan klasifikasi tergolong sedang.